2009
DOI: 10.1021/jp900533k
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evidence for the Ordered Crystallites of Ionic Liquid in Confined Carbon Nanotubes

Abstract: Ionic liquids (ILs) are a class of new green materials that have attracted extensive attention in recent decades. Many novel properties not evident under normal conditions may appear when ionic liquids are confined to a nanometer scale. As was observed in the experiment, an anomalous phase behavior from liquid to high melting point perfect crystal occurred when 1-n-butyl-3-methylimidazolium hexafluorophosphate ([bmim][PF 6 ]) ionic liquid was confined in a carbon nanotube. In this work, we performed molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
99
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 54 publications
10
99
0
Order By: Relevance
“…We used this bulk value due to a lack of more detailed data in the literature for this particular IL, which should act as the foundation for our comparison. Additionally, no particular confinement effect is expected, since the tubular area in our CNT is considerably larger than that of a thin CNT, where the available space in the tube and the hydrogen bond length become comparable 38,39 . The thermal conductivity of the shell λshell was measured to be 28 W/mK and tot A is the total conducting surface of the composite expressed as:…”
Section: Resultsmentioning
confidence: 99%
“…We used this bulk value due to a lack of more detailed data in the literature for this particular IL, which should act as the foundation for our comparison. Additionally, no particular confinement effect is expected, since the tubular area in our CNT is considerably larger than that of a thin CNT, where the available space in the tube and the hydrogen bond length become comparable 38,39 . The thermal conductivity of the shell λshell was measured to be 28 W/mK and tot A is the total conducting surface of the composite expressed as:…”
Section: Resultsmentioning
confidence: 99%
“…Wang 28 illustrated that the compression of the H-bonding between cation and anion in ILs increases the melting point of the nanoconfined IL. Dong et al 20 also performed MD simulation to investigate the ordered ion arrangement of [Bmim][PF 6 ] within the CNTs. The drastic increase in the melting point of C 6 mimBr revealed that the IL within the nanospace is more stable than IL in the bulk system.…”
Section: Resultsmentioning
confidence: 99%
“…Molecules confined inside nanoscale space such as narrow nanotubes or membrane proteins can form one-dimensional (1D) molecular wires, which have attracted intense interest recently because of their scientific importance and potential applications in nanotechnology [1,21,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. Among them, it is of particular interest in determining the structure and dynami-cal behavior of water wires [1,21,[40][41][42][43][44][45][46][47][48][49] which have been found to exist in narrow nanotubes [1,21,[40][41][42][46][47][48] and biological channels [43][44][45].…”
Section: Molecular Wire Of Urea Inside Narrow Carbon Nanotubementioning
confidence: 99%
“…We have calculated the urea flow, defined as the total number of urea molecules per nanosecond that have entered from one end and leave the SWNT from the opposite side. Given that the biological urea channel dvUT [52] has a length of ~ 16 Å (the number of urea molecules accommodated in the selectivity filter is about 3), we chose the 144-carbon (6, 6) SWNT (13.5 Å in length) as the nanochannel, wherein the resulting urea wire also consists of ~ 3 urea molecules. To facilitate a direct comparison with water wire, we performed additional simulations for the SWNT immersed in pure water.…”
Section: Molecular Wire Of Urea Inside Narrow Carbon Nanotubementioning
confidence: 99%